2023
DOI: 10.1519/jsc.0000000000004547
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Exercise at the Critical Heart Rate vs. the Power Output Associated With the Critical Heart Rate

Abstract: Succi, PJ, Dinyer-McNeely, TK, Voskuil, CC, Abel, MG, Clasey, JL, and Bergstrom, HC. Responses to exercise at the critical heart rate vs. the power output associated with the critical heart rate. J Strength Cond Res 37(12): 2362-2372, 2023-This study examined the physiological (volume of oxygen consumption [V Ȯ2 ], heart rate [HR], power output [PO], respiration rate [RR], muscle oxygen saturation [%SmO 2 ]), neuromuscular (electromyographic and mechanomyographic amplitude [EMG AMP and MMG AMP] and mean power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 48 publications
(139 reference statements)
1
15
0
Order By: Relevance
“…The application of HR to the critical power (CP) model to derive the critical heart rate (CHR) [18] has been suggested to provide an individualized, physiologically based threshold that meets the intensity (83-94% HR of VO 2peak ) and duration (>24 min) recommendations for cardiorespiratory endurance training [16,17,19]. The CHR is derived from the linear regression of the total heartbeats (HB Lim ) versus T Lim from multiple exhaustive work bouts at various power outputs.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The application of HR to the critical power (CP) model to derive the critical heart rate (CHR) [18] has been suggested to provide an individualized, physiologically based threshold that meets the intensity (83-94% HR of VO 2peak ) and duration (>24 min) recommendations for cardiorespiratory endurance training [16,17,19]. The CHR is derived from the linear regression of the total heartbeats (HB Lim ) versus T Lim from multiple exhaustive work bouts at various power outputs.…”
Section: Introductionmentioning
confidence: 99%
“…The CHR is derived from the linear regression of the total heartbeats (HB Lim ) versus T Lim from multiple exhaustive work bouts at various power outputs. Previous work [16,17,19] has shown that the decreases in work rate required to maintain HR at CHR results in more sustainable intensities (i.e., longer times to exhaustion (T Lim )) than those anchored by power output yet elicit a metabolic stimulus within the recommended range [16][17][18]. Specifically, exercise at or just below (minus 5 b•min −1 ) CHR was sustained from ~12 to 60 min with metabolic responses maintained (64-88% .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations